2008
DOI: 10.1097/tp.0b013e318187bab0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sirolimus Plus Tacrolimus Versus Sirolimus Plus Cyclosporine in High-Risk Renal Allograft Recipients: Results From an Open-Label, Randomized Trial

Abstract: This study demonstrated that SRL-based therapy was efficacious in high-risk renal allograft recipients in the first year after transplant, providing equivalent efficacy with CsA or TAC, similar graft survival, low biopsy-confirmed acute rejection rates, excellent renal function, and an acceptable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 20 publications
3
30
0
2
Order By: Relevance
“…An overall beneficial effect of mTOR inhibition in APC Min/ þ mice was evident from their ability to maintain weight and not become chronically anemic. The fact that rapamycin treatment did not contribute to the development of anemia also indicates that the dose administered was not toxic, as overdosing of rapamycin can cause bone marrow suppression in humans (Gaber et al, 2008). In addition, rapamycin was administered by incorporating it into their food pellets, and mice never received relatively high daily 'bolus' dosing, as was recently reported (Fujishita et al, 2008).…”
mentioning
confidence: 88%
“…An overall beneficial effect of mTOR inhibition in APC Min/ þ mice was evident from their ability to maintain weight and not become chronically anemic. The fact that rapamycin treatment did not contribute to the development of anemia also indicates that the dose administered was not toxic, as overdosing of rapamycin can cause bone marrow suppression in humans (Gaber et al, 2008). In addition, rapamycin was administered by incorporating it into their food pellets, and mice never received relatively high daily 'bolus' dosing, as was recently reported (Fujishita et al, 2008).…”
mentioning
confidence: 88%
“…14 A significant correlation between the type of immunosuppression used and variations in the incidence and severity of herpetic infections has also been shown in renal transplant recipients. In 2008, Gaber et al 15 compared a group of 224 renal transplanted patients using sirolimus and tacrolimus with another group of 224 patients using sirolimus and cyclosporin, both on corticosteroids for 12 months. Those authors reported a higher incidence of herpes simplex infection among patients using sirolimus and tacrolimus as compared with that of the group using sirolimus and cyclosporin (4.5% and 0.4%, respectively; p = 0.01).…”
Section: Factors F O R the Development O F I N F E C T I O N After Trmentioning
confidence: 99%
“…Pierwsza grupa otrzymywała sirolimus i takrolimus, a druga grupa -sirolimus i cyklosporynę. Wykazano podobny odsetek zakażeń w obu grupach, za wyjątkiem częstszego występo-wania zakażenia HSV w grupie osób otrzymujących takrolimus [36]. W materiale własnym w protokole leczenia immunosupresyjnego pacjenci po przeszczepieniu nerki 3 -krotnie częściej otrzymywali takrolimus niż cyklosporynę, nie mniej odsetek zakażeń w obu grupach był również podobny (47,3% vs 48,6%).…”
Section: Dyskusjaunclassified